Novel methods of teaching psychiatry to medical and postgraduate students. Issue 5 (September 2021) - Jayaram, Mahesh; Shields, Greg; Buisman-Pijlman, Femke
Abstract : Purpose of review: Global burden of mental illness remains at an all-time high and provision of timely good quality care is a challenge globally. Current methods of medical and post-graduate education in psychiatry worldwide have been inadequate in treating those with mental illness. Enormous gaps exist in provision of high-quality teaching, particularly in poorer countries with many having no access to ongoing teaching and training. Recent findings: Technology and changes to curriculum design have transformed student experiences and highlighted the value of online learning. There are many models to consider from and we describe the development process for these, which also highlight why some can be superior to classroom-based learning. New innovations have significantly enhanced engagement and reach thereby bringing students across the globe into an interconnected community and putting them in touch with world experts. Although some of these options may be expensive, many can be made affordable and accessible. Summary: It is possible to use innovations in online education to ensure high-quality teaching is available globally. A high touch model may be suitable when resources permit, and otherwise low touch scalable models provide options for increasing reach. Together, these models provide optimism for improving standards of global psychiatric training.